The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cells11030533
|View full text |Cite
|
Sign up to set email alerts
|

The Translational Bridge between Inflammation and Hepatocarcinogenesis

Abstract: Viral infections or persistent alcohol or drug abuse, together with intrinsic factors, lead to hepatitis, which often ends in the development of liver cirrhosis or hepatocellular carcinoma (HCC). With this review, we describe inflammatory liver diseases, such as acute liver failure, virus-induced hepatitis, alcoholic- and non-alcoholic steatohepatitis, and autoimmune hepatitis, and highlight their driving mechanisms. These include external factors such as alcohol misuse, viral infection and supernutrition, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…mTOR is a critical regulatory factor for environmental and hormonal signals . Adequate nutrition can regulate mTOR to activate anabolic metabolic processes and inhibit catabolic metabolic processes . Recent studies have shown that cholesterol, a fundamental building block of cell growth, is identified as a critical regulator of mTOR activation, which can promote mTOR recruitment to the lysosomal membrane, thus initiating downstream processes, improving anabolism, inhibiting catabolism and ultimately affecting nutrient uptake .…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is a critical regulatory factor for environmental and hormonal signals . Adequate nutrition can regulate mTOR to activate anabolic metabolic processes and inhibit catabolic metabolic processes . Recent studies have shown that cholesterol, a fundamental building block of cell growth, is identified as a critical regulator of mTOR activation, which can promote mTOR recruitment to the lysosomal membrane, thus initiating downstream processes, improving anabolism, inhibiting catabolism and ultimately affecting nutrient uptake .…”
Section: Discussionmentioning
confidence: 99%
“…CCL2, also referred to as monocyte chemoattractant protein 1 (MCP1), triggers chemotaxis, prompting monocytes derived from the peripheral blood or bone marrow to infiltrate into the liver and to differentiate into macrophages [69,70]. This pro-inflammatory environment is enhanced by the release of TNF-α and IL-6 locally in the liver, but is also caused by systemic chronic inflammation processes derived from metabolic tissues such as adipose tissue resulting from insulin resistance [71], and by high leptin but low adiponectin levels, which are typically found in people who are overweight [71,72]. In all, this triggering of the innate immune response marks the transition of simple steatosis to actual steatohepatitis [68,73] and plays a key part in the initiation of NAFLD-related HCC.…”
Section: Inflammatory Pathways In the Pathogenesis Of Nafld And Nafld...mentioning
confidence: 99%
“…NLRP3 activation in hepatic stellate cells (HSCs) promotes the production of the profibrogenic cytokine and induces the expression of the profibrogenic molecule TGF-β. These events in concert lead to liver inflammation and fibrosis, being the link between liver damage and hepatocellular carcinoma [ 38 , 39 ].…”
Section: Pathogenesis Of Hccmentioning
confidence: 99%